Investigation and optimization of a Co-Generation plant integrated of gasifier, gas turbine and heat pipes using minimization of Gibbs free energy, Lagrange method and response surface methodology. (31st July 2020) - Mojaver, Parisa; Jafarmadar, Samad; Khalilarya, Shahram; Chitsaz, Ata
Abstract: A combined plant including a fluidized bed gasifier, a gas turbine, a domestic heat recovery, and heat pipes was proposed and investigated from the first and the second thermodynamic laws and environmental viewpoints. Two types of biomass (wheat straw and rice straw) were fed to the gasifier. A zero-dimensional model was validated against results available in the literature. Gibbs free energy minimization and Lagrange method of undetermined multipliers methods were utilized to obtain the unknown parameters. Effects of steam to biomass ratio of the steam biomass gasification, inlet turbine temperature, and compression ratio were investigated on the plant performances. Analysis of variance results and Pareto chart of the standardized effects were carried out for net power, total exergy efficiency, and carbon dioxide emission of the combined plant. The plant was optimized using response surface methodology. The results indicated that the compression ratio was the most effective parameter and the plant performance was enhanced by increasing the compression ratio. Wheat straw had better performance in comparison with rice straw. Increasing steam to biomass ratio improved the hydrogen production and decreased the cold gas efficiency. Net power was on maximum value at steam to biomass ratio of 1.0, inlet turbine temperature of 1173–1217 K, and compression ratio of 11–12. Highlights: Co-generation plant based gasifier, gas turbine and heat pipe was investigated. Optimization of plant was carried out using response surface methodology. Analysis of variance and Pareto chart of the standardized effects were performed. Wheat straw offered better performance than rice straw.